'Rule Britannia!' – Constructing the National Character in the Eighteenth Century (KULT_online, 2010)
Birgit Neumann’s study Die Rhetorik der Nation (The Rhetoric of the Nation) takes into focus the genre- and media-specific strategies generating national auto- and heteroimages in 18th century Britain. In analysing British identity construction across a wide range of media and genres, she develops a cultural-historical imagology in order to delineate and combine the images' historical variability, cultural functions and media specificity. The national character thus emerges as an intermedial aggregate of topoi, stories and images.